Mesenchymal Hippo signaling regulates intestinal homeostasis in adult mice - Kyvan Dang; Alka Singh; Xin Chen; Jennifer L. Cotton; Susu Guo; Xiaodi Hu; Zhipeng Tao; Haibo Liu; Lihua J. Zhu; Y. Tony Ip; Xu Wu; Junhao Mao (iScience)
Summary: Intestinal homeostasis is tightly regulated by the reciprocal interaction between the gut epithelium and adjacent mesenchyme. The Hippo pathway is intimately associated with intestinal epithelial homeostasis and regeneration; however, its role in postnatal gut mesenchyme remains poorly defined. Here, we find that removal of the core Hippo kinases Lats1/2 or activation of YAP in adult intestinal smooth muscle layers has largely no effect; however, Hippo-YAP signaling in the niche-forming Gli1+ mesenchymal cells plays intrinsic roles in regulating intestinal homeostasis. We find that Lats1/2 deletion drives robust mesenchymal over-proliferation, and YAP activation in Gli1+ pericryptal cells disrupts the intestinal epithelial-mesenchymal crosstalk via promoting Wnt ligand production. We show that YAP is upregulated in the stroma during dextran sodium sulfate (DSS)-induced injury, and mesenchymal YAP activation facilitates intestinal epithelial regeneration. Altogether, our data suggest an important role for mesenchymal Hippo-YAP signaling in the stem cell niche during intestinal homeostasis and pathogenesis.